Longitudinal patterns of companion animals in families with children during the COVID-19 pandemic: Findings from the Adolescent Brain Cognitive Development (ABCD) Study® - King, Erin K.; Dowling-Guyer, Seana; McCobb, Emily; Mueller, Megan K. (Frontiers in Veterinary Science, 2024)
Pet acquisition purportedly increased during the COVID-19 pandemic with individuals acquiring pets during periods of social isolation. Families with children experienced unique challenges during the COVID-19 pandemic, balancing childcare, remote schooling, and other needs and therefore patterns of pet acquisition and loss may differ from the broader population. The goal of this study was to understand patterns of pet ownership within families with adolescents during the pandemic to help identify areas for improved support and programmatic recommendations. Using self-reported survey data from a sample of 7,590 American adolescents from the Adolescent Brain Cognitive Development (ABCD) Study® COVID Survey, we found no evidence for large-scale changes in pet acquisition or relinquishment during the first year of the pandemic for families with adolescents in the U.S. Future research should explore the effects of pet acquisition and pet loss on families with adolescents and what resources are needed to support pet ownership during stressors such as the COVID-19 pandemic.